Variação geográfica no canto de anúncio de Dendropsophus Nanus (Anura, Hylidae) - Annibale, Fabiane Santana [UNESP] (2015)
Anurans communicate information for conspecifics mainly through acoustic signals, whose principal function is reproduction. However, communication system may present geographic variation due to different evolutionary forces. In this study we aimed to test three non-exclusive hypotheses: random drift, environment temperature and body size hypothesis to understand which variables influenced variation in advertisement call of Dendropsophus nanus, a generalist species with large distribution in South America. We sampled nine populations in Cerrado domain in Brazil. The advertisement call of this species is composed by two types of notes: type A, related to male-male competition and type B that may attract females for reproduction so, we analyzed the effect of explanatory variables on each note. Geographical distance and temperature were the main variables explaining variation on both notes. Also we observed differences in the advertisement call among populations between western and eastern localities. As temperature is spatially structured, geographic distance may produce variation in temperature along the longitudinal gradient, reflecting the observed variation in bioacoustic parameters among populations. Body size had effect in variation of type B notes and also we observed that populations occurring in warmer localities presented smaller individuals such as the opposite. We suggest that variation in acoustic parameters may be an indirect result of temperature acting on body size. Therefore we found that the advertisement call of D. nanus present geographic variation due to neutral and ecological processes